Evaluasi Teknis dan Pendampingan Partisipatif dalam Optimalisasi Sarana Sanitasi Tempat Ibadah Berbasis Komunitas - Rif'atul Khusniah; Rofila El Maghfiroh; Kharisma Nur Cahyani; Yehezkiel Septian Yoganata; Yessi Widyasari; Nur Laily Lupita Sari (Forum Kerjasama Pendidikan Tinggi, 2026)
Musholla Al Amin in Rebalas Village, Grati District, Pasuruan Regency, faced sanitation problems related to toilet feasibility, wet-area safety, the arrangement of the ablution area, drainage flow, access to clean water, and facility maintenance practices. The initial condition showed that the musholla had only one toilet unit, slippery wet-area flooring, an unorganized ablution area, poor drainage flow, and no written sanitation maintenance schedule. This community service program aimed to evaluate the technical condition of sanitation facilities and optimize their function through physical improvement, sanitation education, and community-based participatory maintenance assistance. The program was implemented using a participatory technical assistance approach involving 17 participants, consisting of foundation administrators, musholla administrators, local residents, and facility users. Data were collected through technical observation, semi-structured interviews, needs-assessment discussions, visual documentation, pre-test and post-test assessments, and post-program monitoring. The feasibility of sanitation facilities was assessed based on seven indicators: toilet condition, ablution area, access to clean water, drainage system, floor condition, wet-area safety, and facility cleanliness. The results showed that the sanitation facility's feasibility score increased from 35% before the intervention to 85% after the improvement. In the educational aspect, participants’ understanding of healthy sanitation and facility maintenance increased from 15% in the pre-test to 75% in the post-test. In addition, the frequency of facility maintenance increased from an average of once per week to two to three times per week after the education session and the development of a maintenance commitment. These findings indicate that integrating technical evaluation, physical facility optimization, sanitation education, and participatory assistance can improve the sanitation quality of a place of worship while strengthening community involvement in sustaining facility maintenance.